2022
DOI: 10.3389/fphar.2021.834192
|View full text |Cite
|
Sign up to set email alerts
|

Stachytine Hydrochloride Improves Cardiac Function in Mice with ISO-Induced Heart Failure by Inhibiting the α-1,6-Fucosylation on N-Glycosylation of β1AR

Abstract: Background: Cardiovascular diseases have become a major public health problem that seriously threatens human health. The cumulative effects of various cardiovascular events will eventually develop into chronic heart insufficiency and even heart failure, and the β1 adrenergic receptor signal pathway plays an important role in this process. Stachytine hydrochloride is the main active ingredient of Yimucao, which is a traditional Chinese medicine used to treat gynecological diseases. Modern studies have found tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Previous studies showed that STA can improve HF in mice subjected to TAC or isoproterenol [ 5 , 6 , 19 ]. Herein, we recapitulated the cardio-protective effects of STA in TAC mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies showed that STA can improve HF in mice subjected to TAC or isoproterenol [ 5 , 6 , 19 ]. Herein, we recapitulated the cardio-protective effects of STA in TAC mice.…”
Section: Discussionmentioning
confidence: 99%
“…A component of Yimucao (Leonurus japonicas Houtt) is stachydrine hydrochloride (STA), an active alkaloid [4]. STA can attenuate HF induced through pressure overload or isoproterenol in mice [4][5][6]. Currently, the inhibition of hyperphosphorylation of calcium/calmodulindependent protein kinase II (CaMKII) is one of the anti-HF mechanisms of STA [4].…”
Section: Introductionmentioning
confidence: 99%
“…The enzyme α-mannitosidase can affect N-glycan modification on the surface of vascular endothelial cells and thus affect the recruitment and adhesion of inflammatory cells [ 51 ]. Moreover, stachytine hydrochloride (an active ingredient in motherwort granules) can increase the number and N-glycosylation level of β1 adrenergic receptors to activate the cAMP/PKA signaling pathway and improve myocardial function [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, flavonoids isolated from HS aqueous extracts in the present study, such as orientin ( 30 ), vitexin ( 31 ), hyperoside ( 32 ), quercetin ( 33 ), cynaroside ( 34 ), and genistin ( 35 ), have been demonstrated to be cardioprotective during I/R, possibly through a mechanism of regulating mitochondrial function. In addition to flavonoids, other components of HS aqueous extracts, like stachydrine and 3,4-dihydroxyphenylethanol, have also been reported to protect the heart in the models of pressure overload-induced cardiac hypertrophy ( 36 ), ISO-evoked heart failure ( 37 ), and doxorubicin-induced cardiotoxicity ( 38 ). Impressively, the sulfonated diterpenoid derivatives of compounds 23–30 were first reported, and their pharmacological activities and exact chemical structures need to be further elucidated.…”
Section: Discussionmentioning
confidence: 99%